Мodels of Lexical Semantics in the Algorithms for Natural Language Processing - Dilparić, Branislava M.; Perović, Nina (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
The aim of this study was to determine whether some of the approaches of lexical semantics for studying word meaning could be identified in word2vec and recurrent neural networks (RNN), the algorithms for natural language processing (NLP). Linguistic concepts from the field of lexical semantics were decompositional, holistic and relational. Although it is assumed that algorithms for natural language processing cannot be written only on the basis of mathematical knowledge, but also linguistic, this analysis was carried out so as to determine the exact models used in the above-mentioned algorithms.
Keywords: lexical semantics; computational linguistics; decompositional, holistic and relational models; natural language processing; algorithm; word2vec; recurrent neural network